The Adaptation of a Brief Adolescent Subjective Well-Being in School Scale (BASWBSS), the Student Subjective Well-Being Scale in the Indonesian Context [Adaptasi BASWBSS, Skala Kesejahteraan Subjektif Siswa dalam Konteks Indonesia] - Wuri Prasetyawati; Tjut Rifameutia; Robyn Gillies; Peter Newcombe (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
Well-being is an indicator of students’ happiness in school. There is currently a need to identify students’ well-being in order to know the conditions of students’ mental health and their levels of contentment in school. The existing instruments of student well-being in Indonesia have numerous items, which can impact the participants’ behavior in filling out the questionnaires. Therefore, there was a need for a shorter version of the instruments. This research focused on the adaption of the Brief Adolescent Subjective Well-Being in School Scale (BASWBSS), an instrument for subjective well-being with only eight items and was previously developed by Tian, Wang, and Huebner (2015) among high school students in China. A total of 235 Indonesian students, both high school and first-year university students were the participants in this study. Reliability testing using internal consistency, while construct and criterion validity testing was implemented to test this scale's psychometric properties in the Indonesian context. The result of this study indicated that the adaptation of Brief Adolescent Subjective Well-Being in School Scale (BASWBSS) was valid and reliable for Indonesian students. Kesejahteraan merupakan indikator kebahagiaan siswa di sekolah. Saat ini, terdapat kebutuhan mengidentifikasi kesejahteraan siswa untuk mengetahui kondisi kesehatan mental dan tingkat kepuasan mereka di sekolah. Alat ukur kesejahteraan siswa yang ada di Indonesia memiliki banyak butir pertanyaan, yang dapat berdampak pada perilaku partisipan dalam mengisi kuesioner. Karenanya, dibutuhkan versi pendek dari alat ukur tersebut. Penelitian ini berfokus pada adaptasi Brief Adolescent Subjective Well-Being in School Scale (BASWBSS), sebuah alat ukur kesejahteraan subjektif dengan delapan butir yang dikembangkan oleh Tian, Wang, dan Huebner (2015) untuk siswa sekolah menengah atas di Tiongkok. Sebanyak 235 siswa Indonesia, yang merupakan siswa sekolah menengah atas dan mahasiswa tahun pertama, menjadi partisipan dalam penelitian ini. Uji reliabilitas dilakukan menggunakan konsistensi internal, sedangkan uji validitas konstruk dan validitas kriteria digunakan untuk menguji aspek psikometri dalam konteks Indonesia. Hasil penelitian menunjukkan bahwa hasil adaptasi dari Brief Adolescent Subjective Well-Being in School Scale (BASWBSS) valid dan reliabel untuk siswa di Indonesia.